(untitled) (Global Journal of Management and Business Research, 2024)
Abstract- Objective This study plans to analyse the connection between financial performance and the utilization of activity-based cost Accounting System in Industrial Companies in Iraq Methodology Through a cross-sectional mail overview of finance managers information were assembled about the financial performance of the organization the degree of ABC utilization and the empowering conditions that have been noted in the writing as affecting ABC viability As of the finish of 2021 data was accumulated from 50 Baghdad shareholding organizations Results and Findings The relationship between the level of ABC adoption and ABC awareness is examined using regression analysis Furthermore it is utilized to pinpoint the ascent in ROA a proportion of financial performance associated with ABC activities The discoveries show that financial managers have an elevated degree of familiarity with utilizing ABC yet that reception of ABC is low It is likewise found that there is a positive correlation among ABC and an expansion in ROA